1990
DOI: 10.1042/bj2670197
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the lysosomal neuraminidase–β-galactosidase–carboxypeptidase multienzymic complex

Abstract: Lysosomal neuraminidase (sialidase; EC 3.2.1.18) and beta-galactosidase (EC 3.2.1.23), together with a carboxypeptidase, the so-called 'protective protein', were co-purified from the human placenta by affinity chromatography on a concanavalin A-Sepharose column followed by a thiogalactoside-agarose affinity column for beta-galactosidase. Analysis of the purified material by gel-filtration h.p.l.c. revealed three distinct molecular forms, all with high beta-galactosidase specific activity, but only the largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…It was not possible to purify cholerae has demonstrated that this enzyme forms a multi-enzyme complex, which contains other glycosidic and proteolytic activities [36]. Sialidase complexed with other enzymes, including â-galactosidase, is also found in human lysosomes [37]. A similar association may be present with respect to the S. oralis sialidase, whereby glycosidic and proteolytic activities form a multi-enzyme complex.…”
Section: Discussionmentioning
confidence: 84%
“…It was not possible to purify cholerae has demonstrated that this enzyme forms a multi-enzyme complex, which contains other glycosidic and proteolytic activities [36]. Sialidase complexed with other enzymes, including â-galactosidase, is also found in human lysosomes [37]. A similar association may be present with respect to the S. oralis sialidase, whereby glycosidic and proteolytic activities form a multi-enzyme complex.…”
Section: Discussionmentioning
confidence: 84%
“…This protein is incorporated into a multimolecular complex consisting of protective protein and neuraminidase [18]. No molec ular mechanism is known of interactions among these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This serine carboxypeptidase (Galjart et al 1988;Rawlings and Barrett 1994) has at least two distinct functions. First, as demonstrated by copurification experiments (Verheijen et al 1982;Yamamoto and Nishimura 1987;Potier et al 1990;Scheibe et al 1990;Hubbes et al 1992), it associates with the two glycosidases, thereby modulating their intralysosomal stability and activity (Hoogeveen et al 1983;van der Horst et al 1989;Galjart et al 1991). Second, the protein is catalytically active as a lysosomal cathepsin at acidic pH, as well as a deami- Cotresponding authot. dase/esterase at neutral pH, and has been shown to par ticipate in the inactivation of selected neuropeptides like substance P, oxytocin, and endothelin I (Jackman et al 1990;Galjart et al 1991;Jackman et al 1992;Hanna et al 1994).…”
mentioning
confidence: 99%